Statistical optimization for the production of D-mannose isomerase by Saccharothrix sp. CMU-K747 using response surface methodology - Siangsuepchart,A. (Chiang Mai University, 2015)
© 2015, Chiang Mai University. All rights reserved. Response surface methodology (RSM) and central composite design (CCD) were employed to find the optimal fermentation medium for producing intracellular D-mannose isomerase (D-MI) using Saccharothrix sp. CMU-K747. The two variables involved in this study were D-mannose and soybean meal. The statistical analysis of the results showed that, only D-mannose had a significant effect on D-MI production. The optimized medium containing (% w/v) D-mannose, 1.3 and soybean meal, 0.055 resulted in 1.32-fold enhanced in D-MI (1.638 Unit/ml) production compared to the initial level (1.243 Unit/ml). In addition, the effects of incubation period, pH and temperature of D-MI production in the optimized medium composition were also described. This present study is the first report on statistical optimization of medium components for D-MI production and also explored the possibility of using D-MI produced by Saccharothrix sp. CMU-K747 for rare sugar production.